Bāṃlā chandacintāra kramabikāśa - Sen, Prabodh Chandra (Aṇimā Prakāśanī, 1978)
Historical study of the evolution of Bengali metrics from the 12th to the 18th century; lectures delivered at the University of Calcutta, 1972.